2021
DOI: 10.3390/molecules26144235
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive Effect of Cratoxylum formosum (Jack) ssp. pruniflorum on Initial Stage Hepatocarcinogenesis in Rats

Abstract: Cratoxylum formosum ssp. pruniflorum (Kurz) Gogelein (CP) is an indigenous plant found mainly in southeast Asia. Several in vitro studies have confirmed its activity against hepatocellular carcinoma; however, in vivo studies of the effect of CP on liver cancer are needed. This study investigated the effect of CP on early-stage hepatocarcinogenesis in rat liver when using diethylnitrosamine (DEN) as a carcinogen. Immunohistochemistry was used to detect (a) upregulation of glutathione S-transferase placental (GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…There are reports where there is a decrease in the expression of BAX and an increase in the expression of BCL-2 [16,31,32,42,53]. These are accompanied by an increase in the expression of HGF and PCNA, indicating an increase in hepatocyte proliferation [16,33,54]. In this sense, in the DEN+2-AAF group, we only observed a downward trend in BAX expression with no changes in BCL-2 and upward trends in HGF and PCNA expression when compared to the CTL group.…”
Section: Discussionmentioning
confidence: 42%
“…There are reports where there is a decrease in the expression of BAX and an increase in the expression of BCL-2 [16,31,32,42,53]. These are accompanied by an increase in the expression of HGF and PCNA, indicating an increase in hepatocyte proliferation [16,33,54]. In this sense, in the DEN+2-AAF group, we only observed a downward trend in BAX expression with no changes in BCL-2 and upward trends in HGF and PCNA expression when compared to the CTL group.…”
Section: Discussionmentioning
confidence: 42%
“…Evaluation of the SI value for any research on herbal drugs and/or isolated compounds is crucial for determining whether further research should be carried out. 18 Jantamat et al, 19 proposed a lower SI value (>3) for classifying prospective anti-cancer samples. The test results revealed that the n-hexane and ethyl acetate fractions had SI values of 4.21 in T47D cancer cells, followed by the n-hexane fraction with SI values of 16.41 in MCF-7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Since GSTs are a group of hepatic multifunctional proteins participating in the detoxification of toxic and mutagenic agents, the formation of GST-P positive foci depicts the early phase of carcinogenesis due to the enhancement of the detoxification process [ 29 ]. Moreover, apoptosis is increased during carcinogenesis as a countermeasure against precancerous cells to prevent excessive cell proliferation [ 30 ]. Apoptotic cell death was, therefore, measured to confirm the early stage of cancerous formation.…”
Section: Discussionmentioning
confidence: 99%